A Rare Case of Penetrating Trauma Resulting in Isolated Third Nerve Palsy. (2nd January 2016) - Story, Caleb; Patterson, Michael; McWilliams, Wilson; Markowitz, Bethany Bray
ABSTRACT: A 23-year-old male presented to the emergency department with right eye pain, right upper eyelid ptosis, blurry vision, and binocular diplopia that developed immediately after he bent over in a parking lot and the antenna of a car penetrated his right upper eyelid. An extensive workup was performed, and he was found to have an isolated traumatic oculomotor nerve palsy with pupil involvement. No other ocular findings of a traumatic injury were present. The patient was observed for 14 months, during which he continually improved, with almost complete resolution of his diplopia, anisocoria, and ptosis.